Well test analysis for fractured reservoir evaluation - Da Prat, Giovanni (Developments in petroleum science ;, 1990)
The main purpose of this book is to provide the reader with a basic understanding of the behaviour of fractured reservoirs, using evaluation techniques based on processing pressure and flow-rate data resulting from production testing. It covers the fundamental reservoir engineering principles involved in the analysis of fluid flow through fractured reservoirs, the application of existing models to field cases, and the evaluation and description of reservoirs, based on processed data from pressure and production tests. The author also discusses production decline analysis, the understanding of which is a key factor influencing completion or abandonment of a well or even a field. The theoretical concepts are presented as clearly and simply as possible in order to aid comprehension. The book is thus suitable for training and educational purposes, and will help the reader who is unfamiliar with the subject acquire the necessary skills for successful interpretation and analysis of field data. One of the most important features of the book is that it fills the gap between field operations and research, in regard to proper management of reservoirs. The book also contains a computer program (FORTRAN language) which can be incorporated in existing software designed for reservoir evaluation; type curves generation, test design and interpretation, can be achieved by using this program. Petroleum engineers, reservoir engineers, petroleum geologists, research engineers and students in these fields, will be interested in this book as a reference source. It can also be used as a text book for training production and reservoir engineering professionals. It should be available in university and oil company libraries.